Foliar application of molybdenum enhanced quality and yield of crispleaf lettuce (Lactuca sativa L., cv. Grand Rapids) (2018)
Foliar molybdenum (Mo) application may enhance the nitrogen (N) acquisition by the plants and increase the yield and quality of vegetables. A study was conducted to investigate the effect of foliar Mo spray on N nutrition and yield of crispleaf lettuce (Lactuca sativa L., cv. Grand Rapids) grown in the spring-summer period. The experiment was carried out at Ourinhos, São Paulo State, Brazil, from October 2013 to January 2014. Treatments consisted of five Mo rates [0 (control), 25, 50, 75, and 100 g ha–1 of Mo] divided into two foliar sprays, at 14 and 21 days after planting. Foliar application of Mo rates reduced the nitrate (NO3–) concentration, and increased the concentrations of ammonium (NH4+), total N and Mo in the lettuce leaves. These data indicate that the foliar Mo application improved N assimilation of lettuce plants, resulting in less accumulation of NO3– in the leaves and therefore, improving the quality of the vegetable. Number of leaves per plant was not affected by the foliar Mo application. The 55 to 62 g ha–1 of Mo application resulted in increased of the leaves fresh weight (33%), leaves dry weight (28%) and commercial yield (34%) of crisphead lettuce, respectively. Results suggest that Mo deficiency can compromise the N metabolism of plants, and result in lower commercial yield of crispleaf lettuce.